The Relationships of Teacher Ethnic Discrimination, Ethnic Identification, and Host National Identification to School Misconduct of Turkish and Moroccan Immigrant Adolescents in Belgium. Issue 3 (4th March 2017) - D'hondt, Fanny; Eccles, Jacquelynne S.; Van Houtte, Mieke; Stevens, Peter A. J.
ABSTRACT: We focus on school misconduct and how ethnic teacher discrimination, ethnic identification, and host national identification are associated with school misconduct of male and female immigrant adolescents. Additionally, we verify the moderating role of ethnic identification and host national identification. The results show that discrimination and host national identification are related with the school deviance of immigrant adolescents. The relationship between discrimination and school deviance differs for male and female adolescents. Ethnic identification and host national identification only moderate the relationship of ethnic teacher discrimination and school delinquency for girls who experienced ethnic teacher discrimination on a frequent basis.